(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2023)
Reticulofenestra pseudoumbilicus is a Neogene calcareous nannofossil species whose highest stratigraphic occurrence (Top) is a reliable biohorizon in the Pliocene, calibrated at 3.82 Ma. The species is present in the stratigraphic record from at least the Middle Miocene, within an interval around the biohorizon Top Sphenolithus heteromorphus, calibrated at 13.53 Ma, but its lower distribution range is not precisely delineated. The study of nannofossil assemblages in sediment cores from Integrated Ocean Drilling Program IODP Site U1338 (eastern equatorial Pacific) indicates a lower stratigraphic position for the evolutionary emergence (Base) of R. pseudoumbilicus, detected in the Early Miocene with an estimated age of 16.46 Ma. This age results from a new astronomically tuned chronology, which dates the deepest sediments at Site U1338 to 16.67 Ma. Base R. pseudoumbilicus is followed above by a temporary disappearance of the taxon until a re-entrance after 3 Myr. This lengthened stratigraphic range has been confirmed by data from other locations at low and mid-latitudes in the Atlantic. The distribution range of R. pseudoumbilicus, lasting 13 Myr during the Neogene, is thus characterized by a variable pattern of repeated occurrences and disappearances. Comparison to benthic foraminifera δ18O and δ13C records suggests a control by global climatic/environmental conditions on these events, particularly by temperature variations. The recurrent presence of R. pseudoumbilicus at stratigraphically different intervals could represent an example of iterative evolution, expressed as repeated speciation events that are in part influenced by complex external factors related to the dynamic climate and environmental evolution during the Miocene.